Evaluation of Expansion and Maintenance of Umbilical Cord Blood CD34+ Cells in The Co-Culture with Umbilical Cord Blood-Derived Mesenchymal Stem Cells in The Presence of Microcarrier Beads - Sepideh Naseri Mobaraki; Saeid Abroun; Amir Atashi; Saeid Kaviani (Cell Journal, 2023)
Objective: Umbilical cord blood (UCB) is an accessible and effective alternative source for hematopoietic stemcell (HSC) transplantation. Although the clinical application of UCB transplantation has been increased recently,quantitative limitation of HSCs within a single cord blood unit still remains a major hurdle for UCB transplantation.In this study we used microcarrier beads to evaluate the ex vivo expansion of UCB-derived HSCs in co-culturedwith UCB-derived mesenchymal stem cells (MSC).Materials and Methods: In this experimental study, we used microcarrier beads to expand UCB-derived MSCs.We investigated the simultaneous co-culture of UCB-derived CD34+ cells and MSCs with microcarrier beads toexpand CD34+ cells. The colony forming capacity and stemness-related gene expression on the expanded CD34+cells were assessed to determine the multipotency and self-renewal of expanded cells.Results: Our results indicated that the microcarrier-based culture significantly increased the total number and viabilityof UCB-derived MSCs in comparison with the monolayer cultures during seven days. There was a significant increase inthe UCB-derived CD34+ cells expanded in the presence of microcarrier beads in this co-culture system. The expandedUCB-derived CD34+ cells had improved clonogenic capacity, as evidenced by higher numbers of total colony counts,granulocyte, erythrocyte, monocyte, megakaryocyte colony forming units (CFU-GEMM), and granulocyte–monocytecolony forming units (CFU-GM). There were significantly increased expression levels of key regulatory genes (CXCR4,HOXB4, BMI1) during CD34+ cells self-renewal and quiescence in the microcarrier-based co-culture.Conclusion: Our results showed that the increase in the expansion and multipotency of CD34+ cells in the microcarrierbasedco-culture can be attributed to the enhanced hematopoietic support of UCB-derived MSCs and improved cell-cellinteractions. It seems that this co-culture system could have the potential to expand primitive CD34+ cells.